Association of fall risk-increasing drugs with falls in generally healthy older adults: a 3-year prospective observational study of the DO-HEALTH trial - Caroline de Godoi Rezende Costa Molino; Catherine K. Forster; Maud Wieczorek; E. John Orav; Reto W. Kressig; Bruno Vellas; Andreas Egli; Gregor Freystaetter; Heike A. Bischoff-Ferrari; the DO-HEALTH Research Group (BMC Geriatrics)
Abstract Background The association between fall risk-increasing drugs (FRIDs, medications known to be associated with falls) and the number of falls among generally healthy and active community-dwelling older adults is understudied. Prior studies have focused on individual medication classes or have predominantly relied on retrospective assessments of falls. The aim of this study was to investigate the association between FRID use at baseline and the prospective incidence rates of total, injurious and recurrent falls in community-dwelling older adults. Methods This is a 3-year observational analysis of DO-HEALTH, a randomized controlled trial, among community-dwelling adults aged ≥ 70 years without major diseases at baseline. The main exposures were use of at least one FRID and multiple FRIDs (≥ 2 FRIDs) at baseline. The number of total falls (including high- and low-trauma falls, as well as injurious falls) over 3 years of follow-up was defined as the primary outcome, and the number of injurious and the number of recurrent total falls (≥ 2 falls), as the two separate secondary outcomes. To examine these associations, separate negative binomial regression models controlled for the fixed effects of treatment allocation in the DO-HEALTH trial, study site, fall in the last year, age, sex, BMI, and walking aid were used. Additionally, an offset of the logarithm of each participant’s time in the study was included in the models. Results A total of 2157 participants were included, with a baseline median age of 74.0 years, 61.7% of whom were women, and 41.9% having experienced a prior fall in the year preceding enrolment. At baseline, 908 (42.1%) participants used at least one FRID, and 351 (16.3%) reported multiple FRIDs use. Prospectively, over 3 years of follow-up, 3333 falls were reported by 1311 (60.8%) out of the 2157 participants. Baseline use of at least one FRID was significantly associated with increased incidence rates of total falls (incidence rate ratio (IRR) [95% Confidence Interval (CI)] = 1.13 [1.01–1.27]), injurious falls (IRR = 1.15 [1.02–1.29]), and recurrent falls (IRR = 1.12 [1.01–1.23]) over 3 years. These associations were most pronounced among users of multiple FRIDs, with increased incidence rates of total falls (IRR = 1.22 [1.05–1.42]), injurious falls (IRR = 1.33 [1.14–1.54]) and recurrent falls (IRR = 1.14 [1.02–1.29]). Conclusion Our results suggest that FRID use is associated with increased prospective incidence rates of total, injurious, and recurrent falls even among generally healthy older adults. Trial registration DO-HEALTH is registered as NCT01745263 on clinicaltrials.gov, with a registration date of 2012-12-06.